Pengaruh Hard Skill dan Soft Skill Terhadap Kinerja Pegawai Dengan Pelatihan Sebagai Variabel Moderasi Pada Pegawai Lembaga Pemasyarakatan Kelas II A Kota Pekanbaru - Fadhel Ramadhan; Susi Hendriani; Nuryanti Nuryanti (Politeknik Kampar, 2023)
Employee performance is an important element in an organization. Every organization must be able to maintain and improve employee performance. This should also be done by the Pekanbaru Class II A Penitentiary. The purpose of this study was to analyze the effect of hard and soft skills on the performance of employees, with training as a moderating variable. This research was conducted on Class II A Correctional Institution employees in Pekanbaru, totaling 127 employees, using the census method. The data collection technique uses a questionnaire, and the data analysis uses the Structural Equation Model (SEM).The results showed: 1) Hard skills have a positive and significant effect on employee performance; 2) Soft skills have a positive and significant effect on employee performance; 3) Hard skills have a positive and significant effect on employee performance that is moderated by training; and 4) Soft skills have a positive and significant effect on employee performance that is moderated by employee training. Based on the results of the research, the Class II A Penitentiary in Pekanbaru must be able to overcome employee performance problems, especially those related to employee training, hard skills, and soft skills issues.